Pengaruh Pelatihan Kerja dan Insentif Terhadap Kepuasan Kerja dan Dampaknya Terhadap Komitmen (Studi pada Karyawan PT BRI (Persero) Tbk. Malang Martadinata) - Adisaksana, Helmy (Akutansi Bisnis & Manajemen ( ABM ), 2017)
The aim of this research is to know the description about work training, incentive, work satisfaction, and organizational commitment variable and also to know the influence between those variables in PT. Bank Rakyat Indonesia (Persero) Tbk. in the Branch Office of Malang Martadinata. This research takes sample for 52 people/respondents, in which all of them are employee in BRI Bank. Data collection conducted by questionnaire that published to all employees. Research method that used in this research was quantitaive research with descriptive format that aims to describe the relationship or the influence of each variable in the research. To know the influence in this research, then the collected data would be analyzed by using path analysis. Research result shows that: (1) work training variable influenced significantly to the work satisfaction; (2) work training variable influenced significantly to the organizational commitment; (3) incentive variable influenced significantly to the work satisfaction; 4) incentive variable influenced significantly to the organizational commitment; (5) work satisfaction influenced significantly to the organizational commitment.